1979
DOI: 10.1051/rnd:19790507
|View full text |Cite
|
Sign up to set email alerts
|

Défaunation du rumen de mouton

Abstract: (Kurihara et al., 1968 ;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 2 publications
0
25
0
Order By: Relevance
“…Abou Akkada et al (1968) With the objective of studying the role of protozoa on nitrogen recycling within the rumen, a number of attempts were made to defaunate sheep using procedures similar to those described by Bird et al (1978) and Orpin (19'77) and a rumenwashing procedure described by Jouany and Senaud (1919 men, or a rumen-washing procedure de-scribed by Jouany and Senaud (1979). Microscopic counts, on a fresh sample of rumen fluid strained through two layers of cheese cloth, indicated that prior to the experiments a heterogenous population of ciliate protozoa (Fig.…”
mentioning
confidence: 99%
“…Abou Akkada et al (1968) With the objective of studying the role of protozoa on nitrogen recycling within the rumen, a number of attempts were made to defaunate sheep using procedures similar to those described by Bird et al (1978) and Orpin (19'77) and a rumenwashing procedure described by Jouany and Senaud (1919 men, or a rumen-washing procedure de-scribed by Jouany and Senaud (1979). Microscopic counts, on a fresh sample of rumen fluid strained through two layers of cheese cloth, indicated that prior to the experiments a heterogenous population of ciliate protozoa (Fig.…”
mentioning
confidence: 99%
“…About 20 cells of each ciliate species were individually sampled by means of a micropipette from mixed fauna taken from sheep or cows through a rumen fistula or at the slaughterhouse. They were introduced into the rumen of sheep previously defaunated by a technique based on rumen emptying and successive washing (18). Once the population of ciliates reached the minimum level of 10 3 cells/ml in the rumen, the rumen content was sampled and treated for ciliate isolation.…”
Section: Methodsmentioning
confidence: 99%
“…Another way to maintain rumen ciliate protozoa for long periods involves with the rumen of previously defaunated animals (18) into which a few isolated cells of single species are inoculated to obtain monofaunated animals (16,19,21). However, preparing and maintaining a large number of animals in a monofaunated state for a wide range of ciliate strains is difficult.…”
mentioning
confidence: 99%
“…The contents were withdrawn from the reticulo-rumen and kept for 96 h at -20°C according to the method of Jouany and Senaud (1979). The walls of the emptied forestomachs were washed many times with a warm (40°C) NaCl solution (0.9 % w/v) instead of water and the rumen was filled thereafter with 8 1 of a buffer composed of (g/1): NaCl, 0.76; CH 3 COONa, 6.12; H 2 HP0 4 3.48; NaH 2 P0 4 1.38; Na 2 HP0 4 • 2H 2 0, 2.14; NaHC0 3 2.1; MgCl 2 • 6H 2 6, 0.3; CaCl 2 • 2H 2 0, 0.22 and supplemented with 14.7, 15.0 and 16.3 mmol acetic, propionic and butyric acid, respectively.…”
Section: Defaunation Proceduresmentioning
confidence: 99%
“…Linseed oil hydrolysate, Ca0 2 and lactic acid were also applied for defaunation of ruminants (Van Nevel and Demeyer, 1981;Demeyer, 1982;Mondeza et al, 1993). Jouany and Senaud (1979) successfully defaunated sheep by evacuation of rumen contents, washing the reticulo-rumen walls with water and freezing the rumen content to kill the protozoa. To perform our experiments we tried to defaunate sheep by some of the methods mentioned above, but most of them were only partially successful.…”
Section: Introductionmentioning
confidence: 99%